2010
DOI: 10.1159/000317120
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Gender Outcome of Egyptian Patients with 46,XY Disorder of Sex Development

Abstract: Children with disorder of sex development (DSD) may be born with ambiguous genitalia. Decision-making in relation to sex assignment has been perceived as extremely disturbing and difficult to families and health care professionals. This is mainly due to a general paucity of information about the condition and an exaggerated feeling of stigma and shame associated with genital abnormalities. This is the first study in Egypt aimed at studying the psychosexual development and gender outcome of 40 Egyptian patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31). A first report of an Italian population emphasized the importance of differential diagnoses in patients with undervirilization.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31). A first report of an Italian population emphasized the importance of differential diagnoses in patients with undervirilization.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, similar to our observation, they found that there were delays in case referrals due to lack of awareness and sociocultural reasons (3). Other studies in the Middle East, Italy, and Turkey had explored 46XY DSD from different prespectives and reported more or less similar etiology with little variations from our spectrum (7,(30)(31)(32)(33). The expression of the 5-α-reductase iso-enzyme 2 was shown by some molecular studies, as well as some common mutations such as in steroidogenic factor 1 (SF1, NR5A1) and G34R in Egyption patients with 46XY DSD (30,31).…”
Section: Discussionmentioning
confidence: 51%
“…Like 5 α -RD2 deficiency, people with 17 β HSD-3 deficiency are also born with female or mildly masculinized external genitalia despite having a 46,XY chromosomal complement and possessing testes. Also similar to 5 α -RD2 deficiency, genetic males with 17 β HSD-3 deficiency also exhibit an increased incidence of developing a male GI by adolescence despite their initial female rearing [41, 71]. People with either of these conditions in which the biosynthesis of androgens is inhibited due to an enzyme deficiency may have incomplete or full Wolffian duct development and no Müllerian structures.…”
Section: Gi In Major Subcategories Of 46xy Dsdmentioning
confidence: 99%
“…Furthermore, long term outcomes data are lacking for patients with 17βHSD-3 deficiency, especially for those diagnosed at a young age. However, there are a small number of reported cases who were diagnosed in early childhood and retained female gender identity following orchiectomy [10-12]. …”
Section: Introductionmentioning
confidence: 99%